Cinnamon in biocomposite films for antimicrobial food packaging - Martelli, Silvia Maria; Verdan, Maria Helena; Garcia, Vitor Augusto dos Santos [UNESP]; da Silva, Guinevere Siqueira; Aranha, Caroline Pereira Moura; Martins, Vitor Hugo Neto; Souza, Victor Hugo Rodrigues de (Elsevier, 2025)
Foodstuffs are highly vulnerable to contamination caused by microbial pathogens, causing foodborne diseases. Cinnamon is widely used as a food spice, but due to its antibacterial and other pharmacological properties, it can also be used in processing, medicine, and agriculture. Cinnamon essential oil (CEO) exhibits a broad spectrum of antimicrobial and antioxidant effects while restricting the growth of harmful microbes. It can be used as a potential additive in polymer or paper matrixes to increase the shelf life, quality, and safety of the food products they pack. CEO can be directly incorporated within the packaging film in an edible coating, which will be added over foods. There are different ways to incorporate this, such as emulsion systems or CEO encapsulated before incorporation. This chapter provides an overview of different CEO active materials and their potential applications in food to inhibit the growth of pathogens.
Keywords: Active packaging; biopolymers; cinnamon essential oil; composites; food preservation